Peran Perempuan dalam Mewujudkan Keluarga Sukhinah - Trisnadewi, Komang; Kantriani, Ni Ketut; Yogantara, I Wayan Lali; Swarthini, Ni NYoman; Arini, Ni Wayan (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
Harmony, welfare, and family integrity determine the improvement of human resources in the next generation and the progress and peace of the nation and state. Therefore, the principles in the formation of a happy family should be adhered to forever by family members. Every marriage expects a happy family. Guidance is necessary for an effort to realize a happy family, including the people of Pesedahan Village, Manggis District, Karangasem Regency. This method used is in the form of training and practice related to the role of women in realizing a happy family. The role of women emphasized is related to understanding the reproductive system, effective communication methods in the family, and the practice of making ceremonial facilities, namely Banten Tumpeng Pitu and Sanganan Suci. This community service activity went smoothly. Through this activity, participants are expected to have knowledge and understanding and be able to take concrete follow-up actions to create a happy family.